The Relationship between Neutrophil on Lymphocyte Ratio with Clinical Stage of Nasopharyngeal Carcinoma Patients - Nur Fadhila Kurnia; Abdul Qadar Punagi (Faculty of Medicine, Hasanuddin University., 2022)
Introduction: The general objective of this study was to determine the relationship between the ratio of neutrophils to lymphocytes and the clinical stage in patients with nasopharyngeal carcinoma. While the specific goal is to know the characteristics of patients with nasopharyngeal carcinoma. Knowing the description of peripheral neutrophil levels in patients with nasopharyngeal carcinoma. Knowing the description of peripheral lymphocyte levels in patients with nasopharyngeal carcinoma. Knowing the picture of NLR at the clinical stage of patients with nasopharyngeal carcinoma. Methods:The target population in this study were all patients with nasopharyngeal carcinoma. The affordable population is all patients with nasopharyngeal carcinoma who are undergoing treatment at. RSUP. Dr Wahidin Sudirohusodo for the period July 2018 to July 2019.. Results: Based on statistical analysis of the data, this study did not find a significant relationship between the neutrophil-lymphocyte ratio and the clinical stage of nasopharyngeal carcinoma (P = 0.252), even after correcting for sex. Statistical tests were used to see whether or not there was a relationship. between these two variables is the Kruskal-Wallis test, which was chosen because it is a non-parametric comparative test for variables with more than two categories. Conclusions: Based on statistical analysis of the data, this study did not find a significant relationship between the neutrophil-lymphocyte ratio and the clinical stage of nasopharyngeal carcinoma (P = 0.252), even after correcting for sex.